Good growth and governance in Africa rethinking development strategies - Noman, Akbar (Oxford Oxford University Press, 2012)
Why has the economic growth performance of Sub-Saharan Africa been disappointing on balance over the past 50 years? More importantly, what can be done to reverse that trend and to sustain and improve upon the accelerated growth experienced in recent years? What are the possibilities and policies for Africa to reduce poverty and achieve sustained, rapid economic growth? What are the lessons of success in both Africa and elsewhere? Could some of the policies that proved so successful in East Asia help reverse the deindustrialization of Africa in the past three decades and be the basis of its structural transformation?
Includes index
Keywords: Economic development-Africa, Sub-Saharan.